2009
DOI: 10.1016/j.febslet.2009.12.013
|View full text |Cite
|
Sign up to set email alerts
|

The omega‐3 fatty acid, DHA, decreases neuronal cell death in association with altered zinc transport

Abstract: Edited by Jesus AvilaKeywords: DHA Omega-3 fatty acid Zinc ZnT3 M17 human neuronal cell Apoptosis a b s t r a c t Docosahexaenoic acid (DHA) is the major polyunsaturated fatty acid in neuronal cell membranes. We hypothesize that DHA induces a decrease in neuronal cell death through reduced ZnT3 expression and zinc uptake. Exposure of M17 cells to DHA-deficient medium increased the levels of active caspase-3, relative to levels in DHA-replete cells, confirming the adverse effects of DHA deficiency in promoting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 35 publications
(42 reference statements)
3
29
0
1
Order By: Relevance
“…We observed that zinc does in fact get into cells as shown by our 65 Zn studies [20]. The effect of 5 µM of zinc concentration on cell viability was also tested to confirm the occurrence of apoptosis.…”
Section: Methodsmentioning
confidence: 98%
“…We observed that zinc does in fact get into cells as shown by our 65 Zn studies [20]. The effect of 5 µM of zinc concentration on cell viability was also tested to confirm the occurrence of apoptosis.…”
Section: Methodsmentioning
confidence: 98%
“…ZnT and Zip proteins appear to have opposite roles in cellular zinc homeostasis, where ZnT transporters reduce intracellular cytoplasmic zinc by promoting zinc efflux from cells or into intracellular vesicles, while Zip transporters increase intracellular cytoplasmic zinc by promoting extracellular and, perhaps, vesicular zinc transport into cytoplasm (Murakami and Hirano 2008). In M17 cells, we detected the expression of these two zinc transporter families, including Zip1, Zip2, Zip3, Zip4, Znt1, ZnT2, ZnT3, ZnT4, ZnT5, ZnT6 and ZnT7 (Suphioglu, De Mel et al 2010a). ZnT3 has been the focus of our studies, as it is associated with brain zinc accumulation, as well as Alzheimer's disease, the condition where the expression was found to be up-regulated (Zhang, Wang et al 2008).…”
Section: Molecular Link Between Dha and Zinc In Neuronal Cells: Dha Dmentioning
confidence: 90%
“…We therefore used this fundamental idea to investigate the molecular mechanisms underlying the zinc and DHA interaction. With the use of human neuroblastoma cell line M17, we have shown that DHA reduces cellular zinc uptake, possibly mediated by the zinc transporter ZnT3 followed by a significant reduction in pro-apoptotic marker, caspase-3 (Suphioglu, De Mel et al 2010a). This indicates the effect of DHA deficiency in the progression of neurodegenerative disease, which is partly mediated by altered zinc fluxes.…”
Section: Molecular Link Between Dha and Zinc In Neuronal Cells: Dha Dmentioning
confidence: 94%
See 2 more Smart Citations